PENATALAKSANAAN FISIOTERAPI PADA KASUS LANSIA DENGAN PENURUNAN FUNGSIONAL LOW BACK PAIN DI KLINIK ATIK HIDAYATI - Davini Dwi Maycahyasari; Isnaini Herawati; Atik Hidayati; Farid Rahman (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Low Back Pain (LBP) is one of the most common musculoskeletal problems in Indonesian society, with a prevalence rate of 80%. In some patients, the initial acute pain may persist for a period of 3 months and eventually progress to chronic LBP. One method that can be used to treat Low Back Pain Active isometric strengthening exercises can strengthen the anterior oblique muscle group, deep oblique muscle, and back muscle. For hamstrings, lumbar extensors and hip flexors. McKenzie Exercise is an exercise that aims to strengthen the back muscles and relax the abdominal muscles. Objective: to improve functional without discomfort in Low Back Pain clients. Methods: Subjects were given isometric strengthening exercises and McKenzie Exercise for 4 weeks which were carried out 2x/week. Results: Evaluation was carried out using Visual analogue scale and oswestry low back pain measurement instruments. Conclusion: There was an increase in function with a decrease in pain levels during daily activities after being given exercise therapy for 4 weeks.Keywords: Low Back Pain, oswestry low back pain, isometric exercise, McKenzie Exercise.